2010
DOI: 10.1089/jpm.2009.0337
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Age on the Likelihood of Receiving End-of-Life Care Consistent with Patient Treatment Preferences

Abstract: Likelihood of a patient's treatment preference being consistent with care differ by age and treatment preferences. Older patients preferring life-prolonging therapies are less likely to receive them than younger patients; middle-aged patients who want to avoid life-prolonging care are more likely to do so than younger patients. Both findings have implications for patients' quality-of-death, indicating a need for further research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
78
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(90 citation statements)
references
References 37 publications
8
78
3
Order By: Relevance
“…Decisions concerning starting or forgoing life‐prolonging treatments have to be made for many individuals at the end of life. Studies in different populations showed that the majority of individuals prefer treatments to be forgone at the end of life . In some studies, a general preference was asked (e.g., symptom‐directed care versus life‐prolonging care or symptom relief only) .…”
mentioning
confidence: 99%
“…Decisions concerning starting or forgoing life‐prolonging treatments have to be made for many individuals at the end of life. Studies in different populations showed that the majority of individuals prefer treatments to be forgone at the end of life . In some studies, a general preference was asked (e.g., symptom‐directed care versus life‐prolonging care or symptom relief only) .…”
mentioning
confidence: 99%
“…Several recent studies 9, 10,11,12,13,14,15,16,17,18 demonstrate that “demand-side” characteristics (e.g., patient race/ethnicity, age, health status, functional decline, prognostic understanding, treatment preferences, nearby and dependent family members, religious views, spiritual support by religious and medical communities, participation in EOL discussions) are highly significant predictors of aggressiveness of EOL care over and above the effects of the hospital or clinic or regional availability of medical resources in which the care was received. Research has shown that these demand-side characteristics explain more of the variance in geographic and ethnic disparities in the aggressiveness of care than do supply-side characteristics (e.g., hospital bed supply, teaching hospital status, number of medical specialists per capita).…”
mentioning
confidence: 99%
“…The frequency of these latter interventions is far lower than that reported in patients with other cancers (i.e., mechanical ventilation in up to 10% of cases). (4, 28, 29) As compared to controls, hospitalized patients were significantly more likely to have consulted with a chaplain or to have previously participated in a therapeutic clinical trial.…”
Section: Discussionmentioning
confidence: 99%